First principles study of electronic, optical, and thermoelectric properties of K2Pd (Cl/Br)6 for solar cells and renewable energy. (1st March 2022) - Mahmood, Q; Zelai, Taharh; Nazir, Ghazanfar; Albalawi, Hind; Aljameel, A I; Aslam, Imran; Bouzgarrou, S; Mera, Abeer; Hegazy, H H; Alhossainy, M H
Abstract: The vacancy-ordered double perovskites are extensively studied for solar cells and thermoelectric characteristics. Herein, the electronic, mechanical, optical, and transport characteristics of K2 Pd(Cl/Br)6 are addressed comprehensively. The structural, and dynamic stabilities are confirmed by tolerance factors (0.93, 0.95) and the positive frequencies of phonon band structures. The criteria for mechanical stability and elastic parameters ensure their stable, anisotropic, and ductile nature. The computation of band structures (BS) and density of states (DOS) show band gaps 2.0 eV, and 1.3 eV for K2 PdCl6, and K2 PdBr6, respectively. The optical properties are calculated by dielectric constants, absorption coefficient, and their dependent parameters. The K2 PdBr6 has an ideal absorption band for visible light solar cells. The thermoelectric performance has been analyzed by figure of merit (ZT). The positive Seebeck coefficient p-type nature with significantly high ZT (0.73, 0.74) at room temperature.